Honeycomb sandwich composite material structure damage repairing method based on phenolic resin
Through the structural damage repair method of honeycomb sandwich composite materials based on phenolic resin, the problems of long repair cycle, low efficiency and heavy weight gain in the existing technology are solved, and efficient and lightweight repair effects are achieved, suitable for aircraft radomes and The repair of the radome ensures the recovery of structural strength and wave transmission performance.
Patent Information
- Application Number
- CN202411325809.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-23
- Publication Date
- 2025-01-07
AI Technical Summary
The existing honeycomb sandwich composite structural damage repair methods have problems such as long repair cycle, low efficiency, heavy weight gain, high brittleness and poor interface performance, which are especially unable to meet the repair needs of aircraft radomes and radomes.
The structural damage repair method of lightweight, high-wave transmissive honeycomb sandwich composite materials based on phenolic resin is adopted, and through specific material combination and curing processes, including repair surface cleaning, preparation of repair materials, filling and laying, vacuum curing and surface shaping, Ensure that the edge interface of the repair area is good and suitable for emergency repairs in the field.
It achieves the effects of high repair efficiency, good structural strength recovery, and good wave transmission performance recovery, avoids weight gain after repair, and meets the repair needs of aircraft radome and radome.
Smart Images

Figure CN119261252A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of honeycomb sandwich composite material structure damage repair, and in particular relates to a phenolic resin-based honeycomb sandwich composite material structure damage repair method. Background Art
[0002] Honeycomb sandwich composite materials are mainly composed of glass cloth laminates and low-density honeycombs. Due to their good wave transmittance and specific strength and light weight, they are widely used in the manufacture of aircraft radomes, antenna covers and other products. Honeycomb sandwich composite materials have better static performance than ordinary composite laminates, but because their panels are thinner, they are more likely to cause panel depression, delamination, panel and core debonding and even perforation damage when impacted by foreign objects such as bird strikes, hail, and sand and gravel, affecting flight safety. In addition to protecting the internal radar and antenna from mechanical damage and environmental erosion, aircraft radomes and antenna covers also play a rectifying role as part of the aircraft skin structure to maintain the overall aerodynamic shape of the aircraft. The main difficulty in repairing honeycomb sandwich composite materials is that it is necessary to restore its structural strength without changing the aerodynamic shape of the entire aircraft, and to restore its electromagnetic wave transmission efficiency as much as possible to meet the performance requirements of the product itself. Due to the characteristics of honeycomb sandwich composite materials such as complex structural forms, large discrete mechanical properties, diverse damage modes, and high requirements for electromagnetic properties, factors such as material selection, curing process, and patching methods for repair will have a great impact on the quality of repair.
[0003] Conventional repair methods are mostly room temperature curing epoxy resin repairs. For faults such as delamination and debonding, injection and patching methods are usually used for repair. The repair cycle is long, the efficiency is low, the weight increase is large, the repaired part is very brittle, the edge interface performance of the repair area is poor, and it is easy to crack, which affects flight safety and cannot meet the needs of field emergency repairs.
[0004] The Chinese patent with application number 202210859171.4 provides a method for repairing damaged mechanical connections of composite honeycomb sandwich structures. Although it can shorten the repair time, improve the repair efficiency and the operability of field maintenance, the metal patches and blind rivets used in the repair will affect the electromagnetic performance of the product and will cause the problem of increasing the weight of the fuselage. It is not suitable for the repair of aircraft radomes and antenna covers. Summary of the invention
[0005] The purpose of the present invention is to solve the problems of long repair cycle, low efficiency, high weight gain, high brittleness and poor interface performance in the existing honeycomb sandwich composite material structure damage repair method, and provide a lightweight, high-wave-transmitting honeycomb sandwich composite material structure damage repair method based on phenolic resin. The method selects a set of raw and auxiliary materials, forms a complete repair process, determines key repair parameters, and is convenient to operate and has low dependence on equipment. It is suitable for field emergency repairs, has good compatibility with original machine materials, good interface performance at the edge of the repair area, is light in weight, has a high degree of recovery of mechanical properties after repair, and has good recovery of wave transmission performance.
[0006] To achieve the above purpose, the technical solution provided by the present invention is:
[0007] A method for repairing damage to a honeycomb sandwich composite material structure based on phenolic resin comprises the following steps:
[0008] Step 1, pre-processing of the repair area, includes the following sub-steps:
[0009] Step 1.1, cleaning of repair surface: determine the repair scope, mark and demarcate the repair area, and remove the surface coating;
[0010] Step 1.2, preparation of repair surface: remove the skin of the damaged area by step grinding, remove the damaged honeycomb core, clean the repair area and dry it;
[0011] Step 2, preparing a repair material, the repair material includes a honeycomb core and an adhesive film, including the following sub-steps:
[0012] Step 2.1, preparing the honeycomb core: using anhydrous ethanol to adjust the viscosity of the F01-36 phenolic resin glue to 35s-50s, immersing the honeycomb core material GH-1 in the prepared glue and keeping it for a predetermined time, stretching the impregnated honeycomb core, leaving it at 18°C-35°C for 4h-12h and then heating and curing it, so that the glue content of the honeycomb core is between 50% and 60%;
[0013] Step 2.2, preparing the adhesive film: evenly apply the X98-14 phenolic resin adhesive on the flat tooling brushed with the release agent, and let it air-dry until there is no trace of moisture, and the thickness of the adhesive film is 0.08 mm to 0.15 mm;
[0014] Step 2.3, cutting the alkali-free glass cloth, honeycomb core and adhesive film according to the repair area;
[0015] Step 3, filling and laying the damaged part, includes the following sub-steps:
[0016] Step 3.1, replace the skin, including:
[0017] Step 3.1.1, brushing glue nodules: brushing glue nodules on the exposed honeycomb end faces at the damaged parts with X98-14 phenolic resin glue;
[0018] Step 3.1.2, laying: Place the cut adhesive film on the honeycomb end face with the glue nodules, impregnate the alkali-free glass cloth with X98-14 phenolic resin glue, and lay multiple layers. The laying direction is consistent with the original honeycomb direction;
[0019] Step 3.2, replace the honeycomb, including:
[0020] Step 3.2.1, brushing glue nodules: Use X98-14 phenolic resin glue to brush glue nodules on the two end surfaces of the cut honeycomb core patch;
[0021] Step 3.2.2, honeycomb inlay: Apply X98-14 phenolic resin glue on the honeycomb cell wall at the joint of the honeycomb core patch, assemble the adhesive film and the honeycomb core patch and inlay it to the damaged part where the honeycomb core is removed, and place the adhesive film at each of the two end faces of the honeycomb core patch;
[0022] Step 3.2.3, laying: impregnate alkali-free glass cloth with X98-14 phenolic resin glue and lay multiple layers. The laying direction is consistent with the original honeycomb direction and the laying thickness is consistent with the original honeycomb direction.
[0023] Step 4, vacuum curing: prepare a vacuum bag at the repair surface and cure it under vacuum conditions;
[0024] Step 5, surface shaping and polishing;
[0025] Step 6: Restore the surface coating according to the product surface coating requirements.
[0026] Further, in step 1.2, when cleaning, vacuum all dust and debris, clean the repair area with a clean cloth dipped in acetone and let dry.
[0027] Furthermore, in step 3.2.1, after each coat of glue is applied, let it air-dry for 10 to 15 minutes, apply 4 to 6 times, and after the last coat is applied, let it air-dry for more than 1 hour.
[0028] Further, in step 3.1.2, according to 340-380g / m 2 Use alkali-free glass cloth to impregnate X98-14 phenolic resin glue.
[0029] Further, step 4 includes:
[0030] Step 4.1, bag making and vacuuming: laying a porous isolation film, a glue absorbing layer, a non-porous isolation film, and a breathable felt on the repair surface in sequence, and then vacuuming;
[0031] Step 4.2, curing: curing is completed under vacuum conditions using an oven and a vacuum pump.
[0032] Further, step 4 includes:
[0033] Step 4.1, bag making and vacuuming: on the repair surface, a porous isolation film, an adhesive absorption layer, a non-porous isolation film, evenly distributed thermocouples, an electric blanket, and a breathable felt are sequentially laid, and then vacuuming is performed;
[0034] Step 4.2, curing: curing is completed under vacuum conditions using a thermal patching apparatus.
[0035] Furthermore, in step 4.1, EW-100 alkali-free glass cloth is used as the adhesive absorption layer.
[0036] Furthermore, the repair method also includes the steps of mechanical property testing and non-destructive testing between step 4 and step 5.
[0037] Furthermore, the repair method further comprises an electrical performance testing step after step 6.
[0038] The advantages of the present invention are:
[0039] The damage repair method of the honeycomb sandwich composite material structure based on phenolic resin of the present invention adopts a material combination of a specific phenolic resin glue, glass fiber fabric, and honeycomb core material and a matching curing process to complete the impact damage repair of a high-transmittance fiberglass honeycomb sandwich structure. The method is easy to operate, has low equipment requirements, and has high repair efficiency. It is suitable for field repairs, and this material combination and process are consistent with the mechanical performance requirements of most radomes / radomes, can ensure the structural strength of the product, and meet the product usage requirements. Compared with the commonly used epoxy resin room temperature curing repairs such as the infusion method repair and the filling method repair, this material combination and repair method are lighter in weight and avoid the problem of weight gain after repair. In addition, the average wave transmittance of the repaired part can reach more than 92%, and the wave transmittance is good. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] The above and / or other features and advantages of the present invention will become more easily understood through the following description with reference to the accompanying drawings, which are not drawn to scale and some features are exaggerated or reduced to show details of specific components. In the accompanying drawings:
[0041] Figure 1 It is a schematic diagram of repairing the structural damage repair method of the honeycomb sandwich composite material based on phenolic resin of the present invention when replacing the skin;
[0042] Figure 2 It is a schematic diagram of repairing the structural damage of the honeycomb sandwich composite material based on phenolic resin of the present invention when replacing the honeycomb.
[0043] In the figure: 1-inner skin; 2-original honeycomb core; 3-outer skin; 4-new honeycomb core; 5-new outer skin; 6-adhesive film. DETAILED DESCRIPTION
[0044] The present invention will be described in detail below with reference to the accompanying drawings by means of exemplary embodiments of the present invention. It should be noted that the following detailed description of the present invention is only for the purpose of illustration, and is not intended to limit the present invention.
[0045] The present invention provides a phenolic resin-based honeycomb sandwich composite material structure damage repair method, which is used to repair the honeycomb sandwich composite material structure of products such as aircraft radomes and antenna covers when it is damaged. The repair method is easy to operate, has low equipment requirements, high repair efficiency, is suitable for battlefield repairs, and has high strength and good wave transmission after repair, which can meet the product design and use requirements. The entire repair process will hardly cause weight gain problems, which can not only ensure the product repair quality, but also meet the lightweight, convenient and instant repair needs.
[0046] As an exemplary embodiment of the present invention, a method for repairing a honeycomb sandwich composite material structure based on phenolic resin may include:
[0047] Step S1, pre-processing of the repair area;
[0048] Step S2, preparing a repair material, the repair material comprising a honeycomb core and an adhesive film;
[0049] Step S3, filling and laying layers at the damaged part;
[0050] Step S4, vacuum curing: preparing a vacuum bag at the repair surface and curing under vacuum conditions;
[0051] Step S5, performing surface shaping and polishing;
[0052] Step S6, restoring the surface coating according to the product surface coating requirements.
[0053] Step S1 may specifically include:
[0054] Step S1.1, cleaning of repair surface: Use visual inspection, flaw detection, tapping and other methods to determine the repair scope, mark and demarcate the repair area, and remove the surface coating.
[0055] Step S1.2, preparation of repair surface: Remove the skin of the damaged area by step grinding. Then remove the damaged honeycomb core. When removing the honeycomb core, the knife edge should be sharp to avoid tearing the surrounding honeycombs. All dust can be sucked away with a vacuum cleaner, and the repair area can be cleaned with a clean cloth dipped in acetone and dried.
[0056] In step S2, raw and auxiliary materials may be prepared according to the repair material list (see Table 1).
[0057] Table 1
[0058]
[0059]
[0060] Step S2 may include:
[0061] Step S2.1, preparing the honeycomb core: using anhydrous ethanol to adjust the viscosity of the F01-36 phenolic resin glue to 35s to 50s, the viscosity unit (seconds) can be measured by a Tu-4 viscometer, and then immerse the honeycomb core material GH-1 in the prepared glue, and naturally dip it in the glue for 100s to 140s after it is completely soaked. Stretch the impregnated honeycomb core, let it air-dry at 18℃ to 35℃ for 4h to 12h, and then heat and cure it according to the requirements of Table 2.
[0062] Table 2
[0063]
[0064] Check the honeycomb core glue content according to the following formula, which should be between 50% and 60%:
[0065] Honeycomb core glue content = (total weight of honeycomb core after curing - weight of honeycomb core before dipping) ÷ total weight of honeycomb core after curing × 100%
[0066] The honeycomb core can be stored for a long time. The storage temperature is 18℃~35℃, and the relative humidity is not more than 65%. During the storage process, it is necessary to take measures to prevent moisture, dust, heat and squeeze.
[0067] Step S2.2, prepare the adhesive film: evenly apply the X98-14 phenolic resin adhesive on the flat tooling with the release agent. Let it air-dry at 18℃~35℃ until there is no trace of moisture, and the thickness of the adhesive film is controlled at 0.08mm~0.15mm. During the film making process, it should be avoided to apply too thick a layer at one time or to apply too quickly to avoid causing a large number of bubbles and affecting the bonding quality. The prepared adhesive film should be stored in the form of rolls or sheets. The storage temperature is 18℃~35℃, and the relative humidity is not more than 75%. The storage period should not exceed 7 days; dust prevention and isolation measures should be taken.
[0068] Step S2.3, cutting repair materials: cutting alkali-free cloth, preparing qualified honeycomb core and preparing qualified adhesive film according to the repair needs. Cutting vacuum bags, non-porous isolation films, porous isolation films, adhesive absorption layers, breathable felt, sealants and other auxiliary materials.
[0069] Step S3 of filling and laying layers at the damaged part can be divided into the cases of replacing only the skin and replacing both the skin and the honeycomb, which are steps S3.1 and S3.2 respectively.
[0070] For step S3.1, the inner skin 1 and the outer skin 3 sandwich the honeycomb core 2, and the outer skin 3 is damaged and needs to be repaired. Step S3.1 includes:
[0071] Step S3.1.1, remove the skin of the repaired part according to requirement 1.
[0072] Step S3.1.2, brushing glue nodules: When the honeycomb is exposed at the removed part, use X98-14 phenolic resin glue to brush glue nodules on the exposed honeycomb end surface to ensure the bonding performance between the original honeycomb and the new skin. After each brushing, let it air-dry for 10 to 15 minutes, brush 4 to 6 times, and let it air-dry for more than 1 hour after the last brushing.
[0073] Step S3.1.3, laying: place the cut adhesive film 6 on the end surface of the original honeycomb core 2 with the adhesive bumps. 2 Use X98-14 glue to impregnate the alkali-free cloth and lay it in order in a step-by-step manner. The laying direction should be consistent with the original honeycomb direction to form a new outer skin 5. After laying each layer of alkali-free cloth, let it air-dry for more than 15 minutes. When the surface is slightly dry, the next layer can be laid. No wrinkles are allowed after laying. See the laying diagram for details. Figure 1 .
[0074] For step S3.2, if Figure 2 As shown, both the outer skin 3 and the honeycomb core 2 are damaged and need to be repaired. Step S3.2 includes:
[0075] Step S3.2.1, remove the skin of the repaired part and the damaged honeycomb core according to requirement 1.
[0076] Step S3.2.2, brushing glue nodules: Use X98-14 glue to brush glue nodules on the two end surfaces of the newly made honeycomb core 4. After each brushing, let it air-dry for 10-15 minutes, brush 4-6 times, and after the last brushing, let it air-dry for more than 1 hour at a temperature of 18°C to 35°C and a relative humidity of no more than 75%.
[0077] Step S3.2.3, honeycomb mosaic: follow Figure 2 As shown, the assembled embedded adhesive film 6 and the newly made honeycomb core 4 are laid and the adhesive film and honeycomb core patch are embedded in the damaged part where the honeycomb core is removed, and the adhesive film 6 is placed at each of the two end faces of the honeycomb core patch. When assembling and embedding the newly made honeycomb core 4, in order to ensure the interface performance of the new and old honeycombs, X98-14 adhesive is applied to the honeycomb cell wall at the joint, and clamped with tweezers and heated with a hot blower to cure.
[0078] Step S3.2.4, layer laying: The layer laying requirements are the same as those in step S3.1.3 to form a new outer skin 5. The layer laying diagram is shown in FIG. Figure 2 .
[0079] For step S4, the bag making process must be carried out in a controlled contamination area. Before making a vacuum bag, check whether the area where the sealing tape is laid is contaminated. If so, clean it in time to ensure the sealing quality of the vacuum bag, and check whether the vacuum nozzle is blocked and whether the vacuum pipeline is unobstructed. On the repair surface, lay a porous isolation film, an adhesive absorption layer such as EW-100 alkali-free glass cloth, a non-porous isolation film, evenly distributed thermocouples, electric blankets, and breathable felt in sequence to complete the preparation of the vacuum bag. If an oven and a vacuum pump are used to complete the curing, thermocouples and electric blankets are not required during the bag making process. Perform a vacuum check: vacuum to a minimum of 0.08MPa and maintain for at least 15min. Turn off the vacuum system, and the vacuum gauge reading should not drop by more than 0.017MPa / 5min.
[0080] The curing can be completed under vacuum conditions by using an oven and a vacuum pump or a hot patching instrument. The vacuum pressure should be maintained at no less than 0.08MPa and the curing should be completed according to the requirements of Table 3.
[0081] Table 3
[0082] Heating stage From room temperature to 105℃~110℃, the heating rate is no more than 4℃ / min Insulation stage Keep warm at 105℃~110℃ for 120min~125min Heating stage Then heat up to 130℃~135℃, the heating rate is not more than 4℃ / min Insulation stage Keep warm at 130℃~135℃ for 180min~190min Cooling stage Cool down to below 60℃ and take out
[0083] Then in step S5, the repaired surface is polished smooth and cleaned to restore the aerodynamic shape. In step S6, the surface coating is restored according to the product surface coating requirements, and the repaired part is not allowed to be damaged during spraying.
[0084] In some embodiments of the present invention, the repair method further includes a step S of mechanical property testing and nondestructive testing between step S4 and step S5: a mechanical property test piece is made according to the same process and the same batch of materials, and a mechanical property test is performed to ensure the structural strength after the repair. First, the repaired part is tested with a knocking detector, and after passing the test, an ultrasonic phased array detection method is used to perform ultrasonic testing on the repaired part to ensure that there are no defects such as delamination and debonding.
[0085] In addition, an electrical performance test may be performed after step S6: a transmission efficiency test may be performed on the repaired part to ensure that it meets the product transmission efficiency requirements.
[0086] As described above, the present invention uses a specific material combination of phenolic resin glue, glass fiber fabric (alkali-free glass cloth), and honeycomb core material and a matching curing process to complete the impact damage repair of a high-wave-transmitting fiberglass honeycomb sandwich structure. This method is easy to operate, has low equipment requirements, and has high repair efficiency. It is suitable for field repairs, and this material combination and process are consistent with the mechanical performance requirements of most radomes / radomes, and can ensure the structural strength of the product and meet the needs of product use. Compared with commonly used epoxy resin room temperature curing repairs such as infusion repairs and filling repairs, this material combination and repair method are lighter in weight and avoid the problem of weight gain after repair. In addition, the average wave transmittance of the repaired part can reach more than 92%, and the wave transmittance is good.
[0087] Next, the method for repairing damage of a honeycomb sandwich composite material structure based on phenolic resin provided by the present invention is further described with reference to examples.
[0088] In this example, the repair method of the present invention is used to repair the damage of a certain radome, and the implementation steps are as follows:
[0089] The first step is to pre-process the repair area:
[0090] 1. Visual inspection and ultrasonic testing were used to determine the damage location and area. The damage area was approximately 200×200mm, and the damage was in the form of honeycomb collapse.
[0091] 2. Mark the outer contour of the honeycomb damage and determine the repair range according to the number of layers of the original outer skin and the overlap width of the skin. The outer skin of this product is composed of three layers of alkali-free cloth with an overlap width of 10mm. Determine the repair surface and remove the surface coating according to the range that is 30mm larger than the maximum repair range. Use a vacuum cleaner to remove surface debris and clean the surface with clean gauze dipped in acetone.
[0092] 3. Remove the outer skin by step grinding, with a grinding width of 10mm between each layer. Remove the damaged honeycomb core and smooth the honeycomb offset print remaining on the inner skin surface. Use a vacuum cleaner to remove the grinding debris on the surface and the honeycomb core.
[0093] 4. Paste a protective film on the repair surface and take dust and moisture-proof measures. The protective film is not allowed to be opened before the repair process.
[0094] Step 2: Prepare the repair materials:
[0095] 1. Preparation of honeycomb core:
[0096] (1) Preparation of honeycomb core strips: Collect the honeycomb core aramid honeycomb core strips and check whether the material brand and specifications meet the product repair requirements. Check the height and uniformity of the honeycomb core strips. The honeycomb core should be a regular hexagon. At this time, the weight of the honeycomb core strips is 118g. Gently pull the weighed honeycomb core strips apart by hand to make the honeycomb core grid a regular hexagon. If there is local non-adhesive surface bonding, it is allowed to use a pin or a scratching needle to pry it apart.
[0097] (2) Preparation of flat mold: Use acetone or anhydrous ethanol to scrub the working surface of the flat mold to ensure that the surface is clean and grease-free. The working surface temperature should be above 15°C. The working room temperature is 15°C to 32°C, and the relative humidity is ≤75%. Use a clean brush to apply the release agent to the working surface of the mold three times. The interval between each application should be based on the drying time of the release agent. The mold coated with the release agent should be dried for at least 30 minutes before it can be put into use. The brushing range should be about 20mm larger than the actual use range.
[0098] (3) Wearing medical gloves, pour F01-36 varnish into the dipping tank, use anhydrous ethanol to adjust the viscosity of F01-36 glue to 42s, put the honeycomb core blocks into the dipping tank, and gently open each honeycomb grid by hand until the honeycomb core blocks all turn dark brown and naturally dip in glue for 120s.
[0099] (4) Take out the impregnated honeycomb core, stretch the honeycomb core to make it a regular hexagon, let it dry at 23°C for 7 hours, and then take out the honeycomb core.
[0100] (5) Place the honeycomb core on the mold brushed with the release agent, put it into the oven, close the oven door, heat it to 120°C at a rate of 2°C / min, keep it warm for 60 minutes, then heat it to 175°C, keep it warm for 100 minutes, and take it out when it cools to 40°C. The current working room temperature is 23°C.
[0101] (6) The weight of the honeycomb core after curing is 253 g, and the glue content is calculated to be (253-118)÷253×100%=53.36%, which meets the requirements.
[0102] 2. Preparation of film:
[0103] Use a clean brush to apply X98-14 glue thinly and evenly on the flat mold that has been brushed with release agent, let it dry in a 23℃ workroom until there is no trace of moisture, then apply another layer of X98-14 glue, repeat brushing 3 times, randomly select five places on the film to measure the thickness with a micrometer, the average thickness of the film is 0.12mm, which meets the requirements. Store the film in the form of sheets with isolation film in a workroom with a temperature of 18℃~35℃ and a relative humidity of no more than 75%, and indicate the key information such as the film thickness, production time, and validity period.
[0104] 3. Cutting repair materials:
[0105] (1) Cut the newly made honeycomb core in the direction of the original honeycomb as the honeycomb core patch. The size of the honeycomb core patch should be 2mm to 3mm larger than the size of the damaged honeycomb core.
[0106] (2) Cut the same brand of alkali-free glass cloth as the workpiece according to the step-grinding size. The fiber direction of the alkali-free glass cloth should be consistent with the original direction of the machine. Cut 4 layers and mark them. Cut the outermost layer of alkali-free glass cloth with an overlap width of not less than 20mm.
[0107] (3) Cut the adhesive film according to the size of the honeycomb core patch and the size that is 5 mm larger than the outermost alkali-free cloth.
[0108] (4) Cut the porous isolation film and the adhesive absorption layer to a size that is 10 mm larger than the outermost alkali-free glass cloth, and then expand the size by 5 mm to cut the non-porous isolation film and the breathable felt. Finally, cut the vacuum bag to a size that is 20 mm larger than the breathable felt.
[0109] The third step is to fill and lay the damaged parts:
[0110] 1. Brush glue nodules: Brush a small amount of X98-14 glue on both sides of the honeycomb core patch, be careful not to brush into the core grid, and let it air dry for 10-15 minutes after each brushing. Brush 6 times in total. After the last brushing, let it air dry in a clean workroom for 4 hours. Monitor the temperature of the workroom at 23°C and the relative humidity at 42% during the whole process.
[0111] 2. Inlay honeycomb: Place the adhesive film with the same size as the honeycomb core patch on the defective area, and then inlay the honeycomb core patch with glue nodules on both sides in the direction of the original honeycomb. Apply X98-14 adhesive on the honeycomb cell wall at the joint of the new and old honeycombs, clamp with tweezers and heat with hot air to cure. In the process, you can dip a small amount of talcum powder or white carbon black on the tweezers to prevent the tweezers from sticking.
[0112] 3. Layering: Place the adhesive film 5mm larger than the outermost alkali-free cloth on the repair area. Lay the outer skin in order according to the markings, with the amount of glue being 340-380g / m 2 The laying direction is consistent with the original machine. After laying each layer of alkali-free cloth, let it air-dry for more than 15 minutes until the surface is slightly dry before laying the next layer. During the process, you can use a clean brush, scraper, etc. to assist in laying. Check that there are no wrinkles, local lack of glue, or rich glue after laying. After the layers are glued, park in the workshop for 6 hours.
[0113] Step 4: Bag making and vacuum treatment:
[0114] 1. Lay the cut porous isolation film, adhesive absorption layer (EW-100 alkali-free glass cloth), non-porous isolation film and breathable felt on the repair surface in sequence. When laying each layer, you can use paper tape to assist in sticking to avoid falling off and shifting.
[0115] 2. Paste a circle of sealant at a position about 10mm larger than the size of the breathable felt, and place a vacuum nozzle on the edge of the breathable felt, which is slightly smaller than the outline of the sealant.
[0116] 3. Stick the vacuum bag on the sealant. When sticking, straighten the vacuum bag and use a roller to press the sealant and vacuum bag together to avoid air leakage.
[0117] 4. Put the repaired part into the oven, open the side opening of the oven, pass the vacuum tube through, and connect the vacuum nozzle to the vacuum pump outside the oven. When connecting the vacuum pipeline, use a cutting knife to cut the vacuum bag on the surface of the vacuum nozzle groove.
[0118] 5. Vacuum check: Turn on the vacuum pump and check the vacuum degree. If the vacuum degree is not reached, observe the leakage points between the sealant and the vacuum bag, press them tightly and seal them again if necessary until the vacuum pressure exceeds 0.08MPa. Keep it for 15 minutes, then turn off the vacuum pump and check that the vacuum gauge reading drops to 0.006Mpa within 5 minutes, which meets the requirements.
[0119] The fifth step is to carry out curing treatment:
[0120] 1. Close the oven door, set the first stage heating rate to 2℃ / min, curing temperature to 108℃, and curing time to 120min; the second stage heating rate to 2℃ / min, curing temperature to 132℃, and curing time to 185min; the third stage cooling rate to 3℃ / min, and the end temperature to 50℃. Press the start button and start the automatic recording system.
[0121] 2. After the curing is completed, turn off the oven and vacuum pump, remove the package, check whether the curing record meets the curing requirements, and save the data record sheet.
[0122] 3. Use the same batch material combination and process method to make furnace test blocks.
[0123] Step 6: Conduct mechanical property testing and non-destructive testing:
[0124] 1. The test blocks are processed into standard samples with mechanical properties, and static pressure test, flat pull test and tensile shear test are carried out. The test results all meet the mechanical performance requirements of the product.
[0125] 2. The repaired part was tested with a percussion tester and the test result was qualified. Then the ultrasonic phased array test method was used to perform ultrasonic testing on the repaired part, and the test results showed no defects such as delamination and debonding.
[0126] Step 7: Surface shaping and polishing:
[0127] Grind the repair surface to ensure smooth transition. Check that the repaired part should be smooth, flat and have a good aerodynamic shape. There should be no defects such as fuzz, cracks, looseness, etc. The repaired surface is allowed to have honeycomb marks.
[0128] Step 8: Restore the product surface coating:
[0129] Use 320# sandpaper to polish the parts that need to be painted, and clean and dry them with a clean cloth dipped in acetone, and protect the parts that do not need to be painted. Restore the surface coating according to product requirements, and check the thickness of the paint layer layer by layer. The surface is smooth and the color is uniform.
[0130] Step 9: Conduct electrical performance test:
[0131] The transmission efficiency of the repaired part of the product is tested in a microwave darkroom. Both far-field and compact-field tests can be used. A total of 12 frequency points were tested in accordance with the product design and use requirements. The average transmission efficiency was 92.37%, which meets the product's wave-transmitting design requirements.
[0132] This example verifies the effectiveness of the damage repair method of the phenolic resin-based honeycomb sandwich composite material structure of the present invention.
[0133] Finally, it should be noted that the features mentioned and / or shown in the above description of the exemplary embodiments of the present invention may be combined in the same or similar manner into one or more other embodiments, combined with the features in other embodiments or substituted for the corresponding features in other implementations. The technical solutions obtained by these combinations or substitutions shall also be deemed to be included in the protection scope of the present invention.
Claims
1. A method for repairing damage to a honeycomb sandwich composite material structure based on phenolic resin, characterized in that: The following steps are involved: Step 1, pre-processing of the patching area, includes the following sub-steps: Step 1.1, cleaning of repair surface: determine the repair scope, mark and demarcate the repair area, and remove the surface coating; Step 1.2, preparation of repair surface: remove the skin of the damaged area by step grinding, remove the damaged honeycomb core, clean the repair area and dry it; Step 2, preparing a repair material, the repair material includes a honeycomb core and an adhesive film, including the following sub-steps: Step 2.1, preparing the honeycomb core: using anhydrous ethanol to adjust the viscosity of the F01-36 phenolic resin glue to 35s-50s, immersing the honeycomb core material GH-1 in the prepared glue and keeping it for a predetermined time, stretching the impregnated honeycomb core, leaving it at 18°C-35°C for 4h-12h and then heating and curing it, so that the glue content of the honeycomb core is between 50% and 60%; Step 2.2, preparing the adhesive film: evenly apply the X98-14 phenolic resin adhesive on the flat tooling brushed with the release agent, and let it air-dry until there is no trace of moisture, and the thickness of the adhesive film is 0.08 mm to 0.15 mm; Step 2.3, cutting the alkali-free glass cloth, honeycomb core and adhesive film according to the repair area; Step 3, filling and laying the damaged part, includes the following sub-steps: Step 3.1, replace the skin, including: Step 3.1.1, brushing glue nodules: brushing glue nodules on the exposed honeycomb end faces at the damaged parts with X98-14 phenolic resin glue; Step 3.1.2, laying: place the cut adhesive film on the honeycomb end face with the glue nub brushed, use alkali-free glass cloth impregnated with X98-14 phenolic resin glue, and lay multiple layers. The laying direction is consistent with the original honeycomb direction; Step 3.2, replace the honeycomb, including: Step 3.2.1, brushing glue nodules: Use X98-14 phenolic resin glue to brush glue nodules on the two end surfaces of the cut honeycomb core patch; Step 3.2.2, honeycomb inlay: Apply X98-14 phenolic resin glue on the honeycomb cell wall at the joint of the honeycomb core patch, assemble the adhesive film and the honeycomb core patch and inlay it to the damaged part where the honeycomb core is removed, and place the adhesive film at each of the two end faces of the honeycomb core patch; Step 3.2.3, laying: impregnate alkali-free glass cloth with X98-14 phenolic resin glue and lay multiple layers. The laying direction is consistent with the original honeycomb direction and the laying thickness is consistent with the original honeycomb direction. Step 4, vacuum curing: prepare a vacuum bag at the repair surface and cure it under vacuum conditions; Step 5, surface shaping and polishing; Step 6: Restore the surface coating according to the product surface coating requirements.
2. The method for repairing damage to a honeycomb sandwich composite material structure based on phenolic resin according to claim 1, characterized in that: In step 1.2, when cleaning, vacuum all dust and debris, clean the repair area with a clean cloth dipped in acetone and let dry.
3. The method for repairing damage to a honeycomb sandwich composite material structure based on phenolic resin according to claim 1 or 2, characterized in that: In step 3.2.1, after each coat of glue is applied, let it air-dry for 10 to 15 minutes, apply 4 to 6 times, and after the last coat is applied, let it air-dry for more than 1 hour.
4. The method for repairing damage to a honeycomb sandwich composite material structure based on phenolic resin according to claim 1 or 2, characterized in that: In step 3.1.2, according to 340-380g / m 2 Use alkali-free glass cloth to impregnate X98-14 phenolic resin glue.
5. The method for repairing damage of a honeycomb sandwich composite material structure based on phenolic resin according to claim 1, characterized in that: The step 4 comprises: Step 4.1, bag making and vacuuming: laying a porous isolation film, a glue absorbing layer, a non-porous isolation film, and a breathable felt on the repair surface in sequence, and then vacuuming; Step 4.2, curing: curing is completed under vacuum conditions using an oven and a vacuum pump.
6. The method for repairing damage of a honeycomb sandwich composite material structure based on phenolic resin according to claim 1, characterized in that: The step 4 comprises: Step 4.1, bag making and vacuuming: on the repair surface, a porous isolation film, an adhesive absorption layer, a non-porous isolation film, evenly distributed thermocouples, an electric blanket, and a breathable felt are sequentially laid, and then vacuuming is performed; Step 4.2, curing: curing is completed under vacuum conditions using a thermal patching apparatus.
7. The method for repairing damage to a honeycomb sandwich composite material structure based on phenolic resin according to claim 5 or 6, characterized in that: In step 4.1, EW-100 alkali-free glass cloth is used as the adhesive absorption layer.
8. The method for repairing damage of a honeycomb sandwich composite material structure based on phenolic resin according to claim 1 or 2, characterized in that: The steps of mechanical property testing and non-destructive testing are also included between step 4 and step 5.
9. The method for repairing damage of a honeycomb sandwich composite material structure based on phenolic resin according to claim 1 or 2, characterized in that: The method further includes an electrical performance testing step after step 6.
Citation Information
Patent Citations
Composite material honeycomb sandwich structure damage mechanical connection repairing method
CN115257016A